Modernização, agroindustrialização e agricultura familiar : o complexo soja na dinâmica econômica brasileira anos 1970-2000 - Krabbe, Graziela (2010)
This study has pointed out transformations occurred in the Brazilian Agriculture from 70 decade on, going through an intense modernization and industrialization in the countryside, showing, in this study, thoughts of how the changing from rural complex to an agro industry happened in Brazil, Passo Fundo city. Having Soya bean as the flagship. This expansion of modern agriculture comes up at the same time of a constitution of Agro industrial complex, modernizing the technical base of production. Modernization has also brought up a remarkable increase to agricultural production, improving exportation and contributing for National Economy Growth. However, It turned out to be something excluding, because of this, a great number of farmers had very low profit, no to mention the economical crisis during 1980 decade, damaging investments and credits. The economy recovery started at the beginning of 90 s with the insertion of agro diversity as well as family economy which became an income and job source for small business farmers in Soya Bean business. Considering these post crisis transformations, there is new CAI model, inserting agro industries in the diversification question agro diversity, agro ecology, the fortification of family agriculture and the small farm that managed to go through the crisis. Beyond what was mentioned above in this study, it is shown how sensitive Passo Fundo was in respect to all that process, giving a demonstration of correlation with the Macro, which along with the recovery of Soya bean complex and agro diversity, they established themselves into a new brazilian agricultural axis, with all that situation, it is noticed the modernization was satisfactorily carried out. However, these changes have caused serious and irreversible social transformation. The process got maturation related to an intense dynamical agro industrialization in the rural area in which the family agriculture, mostly, was inserted. It was understood that Passo Fundo region was inserted and developed greatly this new model, giving a new concept to its economical characteristic, enhanced by the current agro industrialization